Factor VII Hyperactivity in the Elderly - Kario, Kazuomi; Matsuo, Takefumi; Nakao, Kazukiyo (Thrombosis and Haemostasis, 1991)
To investigate the age-related increase in coagulation factor VII (FVII) and its significance in the elderly, we measured FVII coagulation activity (FVIIc), FVII antigen (FVIIag), and D-dimer levels in 150 normal subjects ranging in age from 60 to 98 years. We also measured blood lipid fractions and serum cholinesterase activity (ChE), os an indicator of hepatic protein synthesis. FVIIc (141 ± 36%), FVIIag(136 ± 28%), and D-dimer (0.150 ± 0.372 αd/ml) levels were significantly higher in the elderly than in younger controls (p <0.01). Both FVIIc and FVIIag levels were significantly higher in elderly women than in elderly men (p <0.01). FVIIc levels significantly correlated with FVIIag levels, but not with D-dimer levels. FVIIag was more closely correlated with ChE levels in both sexes (men: r = 0.425, womenr r = 0.365, p <0.001) than with the lipid fractions. When the elderly subjects were divided into atherosclerotic and nonatherosclerotic groups, both FVIIc (p <0.01) and FVIIag (p <0.05) levels were higher in the former group. Moreover, the FVIIc/FVIIag ratio and ChE levels were higher in both the elderly men and women with atherosclerosis. These results suggest that in elderly subjects, especially with atherosclerosis, hepatic FVII synthesis and the activation of FVII zymogen are both accelerated.